2014
DOI: 10.1038/hdy.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian viviparity: a complex niche in the evolution of genomic imprinting

Abstract: Evolution of mammalian reproductive success has witnessed a strong dependence on maternal resources through placental in utero development. Genomic imprinting, which has an active role in mammalian viviparity, also reveals a biased role for matrilineal DNA in its regulation. The co-existence of three matrilineal generations as one (mother, foetus and post-meiotic oocytes) has provided a maternal niche for transgenerational co-adaptive selection pressures to operate. In utero foetal growth has required increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Imprinted genes, expressed from a single parental allele as a consequence of germline epigenetic events [4], are thought to be the physical embodiment of this conflict. In support of this hypothesis, the number of genes subject to genomic imprinting correlates well with the progressive trend toward internal development and viviparity in mammals with marsupials possessing fewer imprinted genes than the well studied Eutherian mammals, represented by mice and humans [5,6]. Moreover, numerous studies in genetically altered mice have identified imprinted genes that influence fetal weight, placental development, maternal behaviour, lactation and thermogenesis [7][8][9] in a manner generally consistent with the conflict theory.…”
mentioning
confidence: 56%
“…Imprinted genes, expressed from a single parental allele as a consequence of germline epigenetic events [4], are thought to be the physical embodiment of this conflict. In support of this hypothesis, the number of genes subject to genomic imprinting correlates well with the progressive trend toward internal development and viviparity in mammals with marsupials possessing fewer imprinted genes than the well studied Eutherian mammals, represented by mice and humans [5,6]. Moreover, numerous studies in genetically altered mice have identified imprinted genes that influence fetal weight, placental development, maternal behaviour, lactation and thermogenesis [7][8][9] in a manner generally consistent with the conflict theory.…”
mentioning
confidence: 56%
“…Retrospectively, the long gestation period resulting from the adoption of a chorioallantoic placenta allowed extreme brain development in eutherians, whereas marsupials achieved a comparable brain size through an extended lactation period (Ashwell 2008;Weisbecker and Goswami 2010). It has become apparent that several imprinted genes (Keverne 2013(Keverne , 2014 and several LTR retrotransposon-derived genes (Kaneko-Ishino and Ishino 2012, 2015) play important roles in a variety of brain functions. Thus, genomic imprinting and domestication of novel genes have proven to be effective measures for the innovation of therian-and eutherian-specific traits, including viviparous reproduction and sophisticated brain systems.…”
Section: Conclusion: Evolutionary Trade-off In Mammalsmentioning
confidence: 99%
“…Thus, the most prevalent theory suggests that genomic imprinting may have evolved from a conflict between parental genomes, with genes from the father seeking to maximize resource usage and offspring survival, and maternal genes limiting resources to avoid compromising reproductive function while at the same time seeking the viability of all offspring regardless of paternity. Additional theories, not necessarily mutually exclusive, have also been proposed [ 131 , 132 , 133 , 134 ].…”
Section: Dio3 Imprinting In Brain Disease and Ementioning
confidence: 99%